PENGARUH METODE BERNYANYI TERHADAP PENINGKATAN HASIL BELAJAR MATEMATIKA MATERI POKOK KELILING PERSEGI DAN PERSEGI PANJANG SISWA KELAS III MI MUJAHIDIN JATI MULYO KEPUNG - Sri Putrianingsih; Viara Azizah (Center for the Research and the Communicator Service of IAI Hasanuddin Pare-Kediri, 2021)
AbstractThe mind background of this thesis because a low mathematics learning outcomes of students class III in Islamic elementary school Mujahidin Jatimulyo Kepung. It was because so many students’ dislike the mathematic which makes the students less of creativity in answering a question and weak in matter directories, especially in around square and rectangular matters, what makes the students have difficulty of memorizing formulas. On the others, many teacher prefer use the orally to explain the matter of mathematics and asked the students to learn by monotonous method. It based on the relatively of low mathematical average value towards around square and rectangular matters before the reseach was held. In this thesis, reasearcher will use singimg method as an effort to improve students’ mathematics learning outcomes. Hopefully, this ways can help students learning by memorizing formulas easily and motivating students happier in teaching and learning activities which more interesting and fun. The Analytical method used quantitative approach and the type of this reseach is quasi-experimental and helped by SPSS (Statistical Product and Service Solution) version 25 program. The results of the reseach found that in the first problem formulation used Paired Sample t Test. The answer of that is based on the first problem formulation which there is an influence between singing method on improving mathematics learning outcomes of the subject matter around square and rectangular of class III in Islamic Elementary School Mujahidin Jatimulyo Kepung period 2018/2019. It is based on the results of Paired Sample t Test and Post Test experimental class with sig values 0,000<0,05. In the second problem formulation which it is using an Independen Sample t Test. The results of that test which it is there are differences in singing method to improving mathematics learning outcomes of the subject matter around square and rectangular class III in Islamic Elementary School Mujahidin Jatimulyo Kepung period 2018/2019. This is indicated by the results of Independen Simple t Test with sig 2 tailed is 0,000 <0,05.s